Neo sufism and the concept of seven dignities of Muhammad Nafis al-Banjari - Miftah Arifin (AMCA Journal of Community Development, 2021)
This study aims to describe how Muhammad Nafis al-Banjari’s position in transmitting doctrine of wahdat al-wujud in Indonesia. The research used a descriptive form with a qualitative approach and historical method. This study through four stages, namely heuristics, source criticism, interpretation and presentation. Nafis al-Banjari has played a very important role in transmitting wahdat al-wujud thought in Indonesia. Firstly, the thought of wahdat al-wujud tends to be difficult to be understood, but in the next time, it can be explained more easily through the concept of the seven dignities. Nafis al-Banjari then explained the concept The Book of Tuhfah al-Mursalah written by al-Burhanpuri in in his primary book namely Durr al-Nafis.